Judith Nantell. The Poetics of Epiphany in the Spanish Lyric of Today. Bucknell UP, 2019. - Paul Cahill (Studies in 20th & 21st Century Literature, 2020)
Review of Judith Nantell, The Poetics of Epiphany in the Spanish Lyric of Today. Bucknell UP, 2019. ix + 275 pp.
Keywords: Spanish Poetry; Epiphany; Metaphor; Luis Muñoz; Abraham Gragera; Ada Salas; Josep M. Rodríguez